Benign Recurrent Sixth (Abducens) Nerve Palsy following Measles-Mumps-Rubella Vaccination - Areti Bourtoulamaiou; Sohraab Yadav; Harish Nayak (Case Reports in Pediatrics)
Benign, isolated, recurrent sixth nerve palsy is rare in children. It may be associated with febrile viral illness and vaccination in exceptional circumstances although this is a diagnosis of exclusion. Here, we present the case of a 2-year-old Caucasian girl who developed recurrent 6th nerve palsy following vaccination with the measles-mumps-rubella (MMR) vaccine. No underlying pathology was identified following extensive investigations and followup. There is limited data available on the pathophysiology of vaccination-related nerve palsies. As with all previous reports of cranial nerve palsies following vaccination, there was complete resolution in this case. Long term followup with repeated physical examination and investigations is warranted to avoid missing severe pathology and operating unnecessarily.